PENERAPAN ACTIVITY BASED COSTING SYSTEM DALAM EVALUASI PENETUAN TARIF RAWAT INAP PADA RUMAH SAKIT GMC TAMAN SARI - Herry Goenawan Soedarsa; Rosmiati Rosmiati (Universitas Bandar Lampung (UBL), 2019)
The purpose of this study is to add knowledge about the determination of the rates of inpatient services hospitalization with the use of activity based costing, can be used as a reference in setting the service rates of hospitalization in Hospital GMC Taman Sari and as a means of comparison with hospitalization rates that are set for this, as well as being one of the inputs that provide information about activity based costing in its application in a hospital which orientation is the primary community service.This study was conducted on Hospital GMC Taman Sari which is located in the street of Ahmad Yani No. 36 of 20 Km of the Village Taman Sari sub-District Gedongtataan Pesawaran District Lampung Province.The method of analysis used is descriptive method of comparative yaiutu analysis of the tariff of the hospital now, setting method based on activity based costing, then compare the hospitalization rates hospitals based on activity based costing with its realization.The results of the study showed that of perthitungan hospitalization rates using activity based costing, when compared to the rates used by the hospital, then the activity based costing gives a smaller yield.This is due to the overhead of loading on each product. In activity based costing, overhead cost on each product charged on many cost drivers. So in activity based costing, has been able to allocate activity costs to each of the rooms appropriately based on the consumption of each activity.